The Effect of Management Preferences on Audit Quality Empirical Study on a Sample of Audit Firms in The Iraqi Environment (Raparin Journal of Humanities (RJH), 2025)
The current study aims to measure and analyze the nature of the management preferences of audit offices and companies to identify the selection and comparison between different audit offices and firms are made. Besides, it evaluates and analyzes the audit quality offices and companies in the Iraqi context and tests the relationship between the administrative preferences of companies listed on the Iraq Stock Exchange (ISX Henseforth) and the audit quality for audit offices and companies. For achieving the objectives of the study, a main hypothesis directly was adopted to test the relationship between the variables of the study within the framework of the practical side of the study. For this purpose, an applied approach based on evaluation and quantitative mathematical analysis was adopted. Moreover, the annual financial statements of the companies listed on the ISX and the official bulletins of the market were considered as the source of data taking period (2017-2021).The sample of study was mainly represented in a sample of Iraqi audit offices and companies, which amounted to (26) selected audit offices and companies. The sample was selected in the light of identifying and selecting a deliberate sample of the companies subject to audit and listed on the ISX, which amounted to (22) joint stock companies, where the data of those companies was adopted in evaluating the study variables related to the audit offices and companies of the study sample. Based on the collected data and information, a few conclusions are drawn from the results of this study, the most prominent of them was the existence of a relationship and fundamental impact of management preferences on audit quality. The results also showed that the majority of the companies in the study sample preferred to choose the five large audit firms and firms, where the general average percentage of management preferences for the five large audit firms and firms was (68%). This result is much more than the average percentage of their preferences for medium and small audit firms (40%). Among the provided recommendation was the need for the audited companies to realize the importance of choosing an audit company that provides a high-quality service, as this choice is of particular importance to investors, which is align with the market value of the company, by rationalizing the process of making investment decisions, and improving the efficiency of investment in it.